Effect of ducts on the hydrodynamic performance of marine propellers. Issue 2 (15th July 2021) - Liu, Yang; Gong, Qingwei; Bian, Yongning; Suo, Qinghui
Abstract : Purpose: Hydrodynamic forces and efficiency of bare propeller and ducted propellers with a wide range of advance ratio ( J ) and attack angle ( θ ) are examined. The thrust and torque coefficients and the efficiency are presented and discussed in detail. The present results give a reliable guidance to the improvement of the hydrodynamic characteristics of ducted propellers. Design/methodology/approach: The effect of a duct on the hydrodynamic performance of the KP458 propeller is numerically investigated in this study. Finite volume method (FVM)-based simulations are performed for a wide range of advance ratio J (0 ≤ J ≤ 0.75) and attack angle θ of the duct (15° ≤ θ ≤ 45°). A cubic computational domain is employed in this study, and the moving reference frame (MRF) approach is adopted to handle the rotation of the propeller. Turbulence is accounted for with the RNG k - ε model. The present numerical results are first compared against available experimental data and a good agreement is achieved. Findings: The simulation results demonstrate that the hydrodynamic forces and efficiency increases and decreases with J, respectively, at the same attack angle. In addition, it is demonstrated that the hydrodynamic forces and efficiency are both improved due to the presence of the duct, which eventually leads a better hydrodynamic performance at high advance ratios. It is further revealed that as the attack angle increases, the pressure difference between the suction- and pressure-surfaces of the propeller is also augmented, which results in a larger thrust. The wake field is more uniform at θ = 30°, suggesting that a higher efficiency can be obtained. Originality/value: The present study aims to investigate the effect of a duct on the KP458 propeller subjected to uniform inbound flow. The relationship between the uniform incoming flow and the attack angle of the duct is mainly focused, and the design of the ducted propellers for any ship hull can be improved according to this relationship.